PEMBUATAN SISTEM ADMINISTRASI PADA PT.UNGGU FISTA OMEGA - Tiono, Anthony; Santoso, Leo Willyanto; -, Christian (Jurnal Infra, 2013)
PT. Unggul Fista Omega is a company engaged in air transport which is more focus in import and export. Coverage includes shipping worldwide is divided into 9 regions. Regions determines pricing of each shipment is sent. In addition to the area, the type of goods shipped, package type, and the weight of goods shipped by client is another factor in determining the pricing.At the time of recording of data items, the data client, as well as data agent, everything was done manually (recorded in the book), it is an obstacle in making a profit and loss statements, accounts payable and receivables, and to know the status report delivered goods.To help these things, it would require an administrative information system to facilitate the making of profit and loss, loans and receivables, as well as reports the status of the goods shipped. Information System is built using Microsoft Visual Studio 2005.Net and Microsoft SQL Server 2005 as its database. This application features the classification of the value of goods (weight or volume) automatically, calculating the total price automatically and generate reports that are useful to the owner.The conclusion of this application, and the results of the test administration system is to help the owner make it easier to control every transaction there and can obtain the required reports quickly and precisely.